Modulation methods based on phase-shifted PWM for H- bridge multilevel inverters - Lee, Eui Jae; Lee, Kyo Beum (2020 IEEE PELS Workshop on Emerging Technologies: Wireless Power Transfer, WoW 2020, 2020)
This paper analyzes the modulation methods based on phase-shifted PWM (PS-PWM) scheme for cascaded H-bridge multilevel inverter (CHMI). The PS-PWM scheme is one of the modulation schemes for CHMI and it generates same power loss such as switching loss and conduction loss on each cell. However, the PS-PWM scheme leads to the most switching loss than the other schemes for CHMI. Because the switching loss causes failure of power semiconductor switch, it should reduce for reliability of CHMI. In this paper, it is compared and discussed that total harmonic distortion (THD) of modulation methods based on PS-PWM scheme for reducing switching loss. To analyze characteristic each modulation method, the simulation of 3-phase 5-level CHMI is conducted.
Keywords: Cascaded h-bridge multilevel inverters; Conduction loss; Modulation methods; Modulation schemes; Multilevel inverter; Phase-shifted PWM; Power semiconductor switches; Total harmonic distortion (THD); Cascaded H-bridge multilevel inverter; Phase-shifted pulse width modulation method; Switching loss reduction; Total harmonic distortion; Voltage vector